A resistive-capacitive model of pile heat exchangers with an application to thermal response tests interpretation. (August 2019) - Maragna, Charles; Loveridge, Fleur
Abstract: Pile Heat Exchangers (PHE) are an attractive solution to reduce both costs and greenhouse gas emissions for new buildings. However, most state-or-the-art PHE thermal models overlook the heat capacitance of the pile concrete, which is known to be important in thermal analysis. A semi-analytical (SA) model accounting for the pile concrete inertia is developed and validated against a finite-element code. Analysis shows that accounting for PHE inertia always leads to higher performances compared to purely resistive models. Application of the model to interpretation of thermal response tests data allows estimates to be made of the minimum duration test required to obtain reliable values of ground and concrete conductivities. Graphical abstract: Image 1 Highlights: A new finite cylindrical source model with adiabatic surface is developed. A new resistive-capacitive semi-analytical pile heat exchanger model is developed. The new model improves the assessment of pile thermal performance. Neglecting heat capacitance in the pile leads to an underestimation of performance. The new model is successfully used to interpret a thermal response test.